A regularização fundiária em bens públicos sob a ótica da hermenêutica constitucional - Portella, Marcelo Michel (2021)
The study aims to demonstrate that, in the current scenario, land regularization in public assets must be applied from the perspective of fundamental rights, which are part of the very structure of property rights, outlining their concept, exercise and protection. To this end, contextualization with constitutional hermeneutics is necessary here, aiming to launch minimal, but significant, theoretical references that deal with fundamental issues for understanding the right to housing and its socioeconomic implications. Initially, the meaning of interpretation and hermeneutics is observed, and then, understanding the scope of constitutional hermeneutics, endowed with peculiarities that confer distinction from general hermeneutics. The theorists Hans Kelsen, Herbert Hart, Ronald Dworkin, Peter Häberle, Luigi Ferrajoli and Miguel Carbonell, among others, are simply mentioned, highlighting the main aspects of their thoughts regarding the interpretation and application of constitutional norms. The evolution of these thoughts leads to a certainty: the Constitution must be interpreted systematically, encompassing the dominant values, respected and present within society, but, without forgetting the necessary protection of the essential core of the Constitution - the material rules, under the primacy of the principles of constitutional supremacy and unity. In terms of methodology, the study fundamentally presupposes bibliographical research, using the synthetic approach as a method, enabling brief evaluations and personal considerations on constitutional hermeneutics to carry out in-depth research on land regularization in public assets.